2010
DOI: 10.1088/0960-1317/20/10/105006
|View full text |Cite
|
Sign up to set email alerts
|

In-plane silicon probes for simultaneous neural recording and drug delivery

Abstract: This paper reports on the design, fabrication and characterization of silicon-based microprobes for simultaneous neural recording and drug delivery. The fabrication technology is based on two-stage deep reactive ion etching combined with silicon wafer bonding and grinding to realize channel structures integrated in needle-like probe shafts. Liquids can be supplied to microfluidic devices via in-plane and out-of-plane ports. The liquid is dispensed at circular out-of-plane ports with a diameter of 25 μm and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 46 publications
(113 reference statements)
0
76
0
Order By: Relevance
“…Multichannel high-density microprobes have been reported over the past three decades offering advanced capabilities such as three-dimensional (3D) arrays [1,[13][14][15], integrated electronics [16][17][18], integrated biosensors [19,20], and embedded microfluidic channels [21][22][23][24]. Although silicon is the most utilized material [25][26][27][28], other substrates such as metals [29][30][31], sapphire [32], and glass [33] have been employed in the fabrication of microprobes.…”
Section: Introductionmentioning
confidence: 99%
“…Multichannel high-density microprobes have been reported over the past three decades offering advanced capabilities such as three-dimensional (3D) arrays [1,[13][14][15], integrated electronics [16][17][18], integrated biosensors [19,20], and embedded microfluidic channels [21][22][23][24]. Although silicon is the most utilized material [25][26][27][28], other substrates such as metals [29][30][31], sapphire [32], and glass [33] have been employed in the fabrication of microprobes.…”
Section: Introductionmentioning
confidence: 99%
“…7b) (Colas, 2001;Musick et al, 2009). Various neural implant design studies with included microfluidics have already been reported (e.g., (Metz et al, 2004;Suzuki et al, 2004;Seidl & Et al., 2010)) and their benefit been discussed recently (Musienko et al, 2009). Although the stable coupling of the microchannels to outside fluidics might be possible (e.g., by making use of multilayer bonding concepts (Zhang et al, 2010) or reversible mechanical, pressure-or vacuum-assisted interconnection strategies (Chen & Pan, 2011)), without doubt it will be even more challenging than the design of fail-proof electrical connectors as discussed above.…”
Section: Optional Strategies and Future Directionsmentioning
confidence: 99%
“…With MEMS technology, the precise definition of electrode size and shape can be realized, and multiple recording/stimulation sites can be fabricated on a single probe shank [9]. Starting with the pioneering work from Wise et al [10], a growing number of silicon-based electrode arrays have been developed in the past and the performances of MEMS silicon microelectrodes have been improved in many aspects [11,12], e.g., three-dimensional arrays [13,14,15], dual-sided microelectrode arrays [16], integrated electronics or microfluidic channels [17,18,19,20,21,22], silicon probes for optical stimulation and imaging [23,24,25,26,27,28] or neurochemical signals detection [29,30,31]. In addition, one of the most important fabrication advancements is to integrate a greater number of recording sites on a single probe shank and simultaneously minimizing the probe geometry to avoid large tissue damages during the insertion.…”
Section: Introductionmentioning
confidence: 99%